A Survey of Approaches for Designing Course Timetable Scheduling Systems in Tertiary Institutions - Usman Bala Musa; Akinyemi Moruff Oyelakin (Ikatan Ahli Informatika Indonesia Nusantara, 2024)
Scheduling the course schedule in tertiary institutions is a complex and crucial task. Past studies have pointed out that when scheduling is performed effectively, it influences students' learning experiences, faculty workloads, and overall institutional efficiency. It has also been argued that in the allocation of courses, classrooms, and faculty members, various constraints, preferences, assumptions, dependencies, and objectives must be taken into consideration. This article reviewed different approaches that have been employed in designing course schedule scheduling systems with particular reference to tertiary institutions. Relevant articles were sourced from notable research repositories using identified keywords. The articles obtained were categorized according to the different methods that were used to solve the scheduling problems of course schedules in higher institutions. The review evaluated how each approach addresses the challenges in course time table scheduling. Thereafter, the paper discussed the advantages, limitations, and suitability of these scheduling techniques time-tabling. Additionally, real-world implementations in various tertiary institutions are mentioned. By discussing the strengths and weaknesses of different methodologies in this work, this survey is believed to be a valuable resource for future studies in the area of course scheduling in tertiary institutions.